2020
DOI: 10.17222/mit.2019.198
|View full text |Cite
|
Sign up to set email alerts
|

Formation and influence of magnesium-alumina spinel on the properties of refractory forsterite-spinel ceramics

Abstract: Forsterite refractory ceramic is mostly used in the cement industry as the lining of a rotary kiln and as the lining of metallurgical furnaces due to its high refractoriness of up to 1850°C. Another significant property of forsterite is its coefficient of linear thermal expansion used in the electrotechnical industry for ceramic-metal joints. An addition of aluminium oxide to a raw-material mixture results in the creation of a magnesium-alumina spinel (MgO•Al2O3), which improves the sintering and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…In the first stage, there was a linear expansion of raw materials that occurred up to 1000 • C, which was then followed by a shrinkage stage in the temperature interval of 1000-1250 • C. The third stage observed an expansion in the temperature interval 1250-1350 • C, which was caused by mullite crystal growth and reaction with magnesium oxide to form spinel, leading to the creation of the liquid glass phase. This behavior was also reported in other works [17,21] and previous research [22,23]. The fourth stage occurred at temperatures above 1350 • C and caused re-shrinkage due to the sintering promotion action of the liquid glass phase [17,21].…”
Section: Thermal and Thermo-mechanical Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…In the first stage, there was a linear expansion of raw materials that occurred up to 1000 • C, which was then followed by a shrinkage stage in the temperature interval of 1000-1250 • C. The third stage observed an expansion in the temperature interval 1250-1350 • C, which was caused by mullite crystal growth and reaction with magnesium oxide to form spinel, leading to the creation of the liquid glass phase. This behavior was also reported in other works [17,21] and previous research [22,23]. The fourth stage occurred at temperatures above 1350 • C and caused re-shrinkage due to the sintering promotion action of the liquid glass phase [17,21].…”
Section: Thermal and Thermo-mechanical Analysessupporting
confidence: 89%
“…Despite the utilization of fly ash in the synthesis of aluminosilicate refractories, little research has been carried out on the use of fly ash in the synthesis of other refractories containing silicon and/or aluminum oxides, such as forsterite-spinel ceramics. The mullite-containing fly ash decomposes into silica and alumina in the presence of flux oxides, and these, together with magnesium oxide, form spinel, as proven by both the literature [17][18][19] and previous research [22,23]. Magnesium-alumina spinel is used with magnesia as a lining in cement and lime kilns because of its high melting point of 2135 • C, low thermal expansion coefficient in comparison with forsterite and good thermal shock, chemical and corrosion resistance [9,12,13].…”
Section: Introductionmentioning
confidence: 95%
“…Předchozí výzkum také prokazuje úspěšné využití popílku jako zdroje oxidu hlinitého pro syntézu forsterit-spinelové keramiky. [11,12]…”
Section: úVodunclassified
“…However, this adverse effect of forsterite ceramics can be reduced by the incorporation of magnesium alumina spinel (MgO•Al 2 O 3 ) directly into the raw material mixtures or indirectly by the addition of aluminum oxide as a raw material and its subsequent synthesis with magnesium oxide for the creation of spinel. Previous authors' studies have explored the feasibility of synthesis of spinel from the addition of raw materials containing aluminum oxide into forsterite mixtures [14,15]. Refractory spinel ceramics are also widely adopted in various fields, predominantly as linings of various industrial kilns and furnaces due to their numerous advantages, i.e., a very high melting point of 2135 • C, a low coefficient of thermal expansion compared to coefficient of forsterite, better thermal shock resistance, and chemical and corrosion resistance [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proven that spinel incorporation into forsterite ceramics has been shown to improve physico-mechanical properties such as microstructure, mechanical properties and thermal shock resistance due to the embedment of spinel crystals that are located predominantly near the grain boundaries of larger forsterite crystals or bound in the amorphous matrix and filling the empty sections of cavities and pores in between [14,15,21].…”
Section: Introductionmentioning
confidence: 99%